Transitioning from Lupus Low Disease Activity State to remission in systemic lupus erythematosus: real-world evidence - Gao, Dai; Ji, Lanlan; Zhang, Xiaohui; Hao, Yanjie; Xie, Wenhui; Fan, Yong; Zhang, Zhuoli (Frontiers in Immunology, 2025)
ObjectivesTo identify predictors and barriers to achieving remission in systemic lupus erythematosus (SLE) patients after attaining Lupus Low Disease Activity State (LLDAS).MethodsThis study included patients from the Sle to TARget (STAR) cohort who did not fulfill LLDAS at baseline. The Kaplan-Meier method was used to estimate the cumulative probabilities of remission or flare after LLDAS attainment. Univariate and multivariable Cox proportional hazards models were employed to identify predictors of time to remission. Barriers impeding remission achievement were also investigated.ResultsOf 586 enrolled patients, 480 achieved LLDAS within 20.4 months (IQR 13.4-37.1). Among these, 369 patients who did not achieve remission simultaneously with LLDAS attainment and had ongoing follow-up were included in further analysis. Subsequently, 297 (80.5%) patients achieved remission, with median times to remission and flare of 12.4 and 24.4 months, respectively. Independent predictors of a shorter time to remission included older age at disease onset (HR 1.012, 95%CI=1.004-1.020, P=0.002), arthritis (HR 1.481, 95%CI=1.113-1.969, P=0.007), and gastrointestinal involvement (HR 1.994, 95%CI=1.230-3.232, P=0.005). Conversely, anemia (HR 0.564, 95%CI=0.428-0.743, P<0.001) was a risk predictor. Higher disease activity defined by SLE Disease Activity Index 2000 (HR 0.691, 95%CI=0.632-0.757, P<0.001) or the Physician’s Global Assessment (HR 0.062, 95%CI=0.031-0.127, P<0.001) and the presence of rash (HR 0.156, 95%CI=0.049-0.499, P=0.002), anti-dsDNA positivity (HR 0.513, 95%CI=0.403-0.654, P<0.001), hypocomplementemia (HR 0.468, 95%CI=0.346-0.632, P<0.001), or thrombocytopenia (HR 0.138, 95%CI=0.051-0.377, P<0.001) at the time of LLDAS attainment also demonstrated negative associations with remission. Patients maintaining hydroxychloroquine (HR 1.662, 95%CI=1.115-2.477, P=0.013) or cyclophosphamide (HR 3.468, 95%CI=1.959-6.141, P<0.001) regimens at LLDAS exhibited a shorter time to remission. Moreover, 68.7% of patients failed to achieve remission at the visit preceding remission solely due to prednisone doses of ≥5 mg/day, while other criteria impeded only 5.7-8.4% of cases.ConclusionsAchieving rapid remission after LLDAS attainment remains challenging for most SLE patients, mainly due to difficulties in reducing prednisone dosage to ≤5 mg/day.